Benefit-cost analysis and socio-economic considerations of trypanosomiasis control and treatment in Northern Ghana - Salifu, W.; Asuming-Brempong, S.; Al-Hassan, R.M. (African Journal of Agricultural Research, 2010)
The paper estimated the cost of tsetse control and treatment of trypanosomiasis and the benefits involved, using benefit-cost analysis. It also estimated the extent to which socio-economic characteristics of farmers affect the use of tsetse control techniques, using a maximum Likelihood-Binary Logit model. The results showed that farmers will benefit if they invest in control and treatment of the disease. We found that the farmer accepting the challenge that the tsetse fly is a threat to cattle production, the number of dependants the farmer has, and the farmer agreeing that the bite of the tsetse fly causes the nagana disease were significant factors that affect adoption of control practices including the use of prescribed drugs. Our findings suggest that there is potential for farmers’ response and participation in tsetse control activities in Northern Ghana. What seems to be lacking is the relevant information that farmers need to encourage them to participate. We recommend therefore that more extension services should be provided to livestock farmers to help them derive maximum benefit from disease control practices.
Keywords: Savelugu/Nanton; Socio-Economic; Trypanosomiasis; Tsetse fly; Benefit-Cost Analysis